The Role of Corporate Governance in Moderating the Influence of Company Growth and Size on Corporate Social Responsibility Disclosure - Khafid, M; Baroroh, N; Firmansyah, M (KnE Social Sciences, 2018)
The purpose of this study is to obtain empirical evidence about the moderating effect of corporate governance on the effects of growth and firm size towards corporate social responsibility disclosure.The population is registered as a participant of Corporate Governance Perception Index (CGPI) award 2013-2014 from 47 companies. The sampling technique used in this research is purposive sampling. Nineteen (19) companies were selected in this research with 38 of units of analysis were observed. Regression analysis absolute value of the difference was used for analyzing the data. The results indicate that corporate governance increases the significant effect of company’s growth and size to CSR disclosure. This research is using the corporate governance as the moderating variable which is rare to be employed in this area of research. Keywords: company growth; corporate governance; environmental disclosure, JEL: G32; M41.